Learn Blackberry Games Development - Hamer, Carol; Davison, Andrew (Apress : Imprint: Apress, 2010)
BlackBerry smart phones aren't just for business. In fact, throw away that boring spreadsheet, tear up that yearly budget report-the BlackBerry is a lean, mean game-playing machine. Carol Hamer and Andrew Davison, expert software game developers, show you how to leverage the BlackBerry Java™ Development Environment (based on Java ME) to design and create fun, sophisticated game applications from role playing to dueling with light sabers. The BlackBerry: not as clumsy or as random as a blaster-an elegant device, for a more civilized age. In this book, Carol and Andrew give you the professional techniques you need to use music, 2D and 3D graphics, maps, and game design patterns to build peer-to-peer games, role playing games, and more for the BlackBerry.